Os efeitos do laser de baixa intensidade e do Biosilicato®, utilizados independentemente ou associados, sobre o reparo ósseo em ratas osteopênicas - Fangel, Renan (Universidade Federal de São Carlos, 2009)
Osteoporosis is generally a systematic skeletal disease characterized by low bone density and microarchitectural deterioration of bone tissue with a consequent increase in bone fragility. Osteopenia is characterised by a lower bone density than normal bone tissue but higher than osteoporotic bone tissue. Osteoporosis and osteopenia represent a severe health threat to elderly people and they have recently been recognised as a major public health problem. They are related with some clinic manifestations, mainly the increase of the fractures risk. In this context, there is a critical need to develop technologies able of treating osteoporotic and osteopenic fractures. Promising treatments are the use of biomaterials and the Low Level Laser Therapy (LLLT), which seem to induce osteogenesis and stimulate fracture healing. The aim of this study was to determine the effects of the Biosilicate® and the LLLT on bone consolidation of osteopenic rat. Seventy female Wistar rats (12 weeks-old, ± 250g) ovariectomy (OVX) was carried on. The animals were randomly divided into 7 groups, with 10 animals each: standard control (CP); defect bone control (CD), bone defect treated with Biosilicate® (B), bone defect treated with laser 60J/cm2 (L60), bone defect treated with laser 120J/cm2 (L120), bone defect treated with both treatments Biosilicate® and laser 60J/cm2 (B+L60), bone defect treated with both treatments Biosilicate® and laser 120J/cm2 (B+L120). Sixty days post-OVX the osteotomies were surgically performed on the left tibia. In the Biosilicate® treated animals, the cavities were carefully filled with the biomaterial. An 830nm laser was performed for seven sessions. On day 14 post-osteotomy, rats were sacrificed and the tibias were defleshed. Biomechanical properties of the tibia were determined by two tests: the Indentation Test to a depth of 0-0.5mm, 0-1.0mm and 0-1.5mm and the Three-Point Bending Test. From de load-deformation curve, the maximal load (KN) and energy absorption (J) were obtained. Statistical analyses were performed using Kruskal-Wallis Test and Mann-Whitney U Test, with the level of significance of 5% (p≤0.05). In relation to biomechanical properties of the Indentation Test, the groups CP, B, B+L60 and B+L120 presented higher statistically values (p<0.05) in relation to group CD. The better biomechanical answer among the groups was present by the group with Biosilicate® utilization in association of 120J/cm². In relation to maximal load of the Three-Point Bending Test, the group L60 presented higher statistically values (p< 0.05) in relation to group CP, B, L120, B+L60, B+L120 and the groups had similar values of absorption energy. The Biosilicate® application raised the biomechanical properties of the callus bone, but didn t raise the biomechanical properties of the tibia determined by Three-Point Bending Test. In the two biomechanical tests, the groups with treatment based only on laser irradiation haven t presented significant results in relation to group control fracture. The bones defects treated with both treatments Biosilicate® and laser 120J/cm2 presented higher biomechanical properties of the callus bone in relation to the group based only Biosilicate® application.
Keywords: Fisioterapia; Fototerapia; Biomateriais; Reparo ósseo; Terapia laser de baixa intensidade; Propriedades biomecânicas; Fracture healing; Biomaterial; Low level laser therapy; Biomechanical properties; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL